Comparison of salivary alpha-amylase levels in gingivitis and periodontitis - Dyah Nindita Carolina; Yanti Rusyanti; Agus Susanto (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: The development of periodontal disease is influenced by bacteria-plaque, while there are also several factors modifying the host’s response, one of which is psychological stress. Alpha-amylase as a biomarker is also associated with periodontal inflammatory disease. Purpose: The purpose of this study was to examine the difference of alpha-amylase level between gingivitis and periodontitis. Methods: This research constitutes a descriptive study involving 44 subjects, divided into two groups: one of 22 gingivitis subjects and the other of 22 periodontitis subjects. These individuals completed a PSS-14 questionnaire before their levels of alpha salivary amylase were measured by Cocorometer. Data was analyzed by means of a paired T test and a Mann Whitney test with p < 0.05. Results: There were significant differences between the alpha-amylase levels of gingivitis and periodontitis. However, no significant contrast existed in the PSS-14 scores of the two periodontal disease groups. Conclusion: In conclusion alpha-amylase levels in the periodontitis group were higher than those in the gingivitis group and could be used as marker indicators of stress.